Seasonal emergence of chironomids in relation to egglaying and hatching of ducks in a restored lake (northern Sweden) - Danell, Kjell; Sjöberg, Kjells (Wildfowl, 1977)
The emergence of chironomids was studied using ten emergence traps in Lake Veittijrvi, northern Sweden. The lake (45 hectares) was drained about 1930 and the exposed dry bottom soon became covered by sedges, but they were killed after flooding in 1971. At least 12 chironomid species have colonized the lake and are abundant (about 2,000 larvae per m^2) at the present stage. Their emergence started about ten days after thawing and was concentrated to a relatively short period in late May and early June. Most of the breeding dabbling duck females had completed egg-laying (a period during which they usually consume large quantities of invertebrates) before the time when adult chironomids became abundant. The hatching of ducklings (Teal Anas crecca, Pintail A. acuta and Mallard A. platyrhynchos) was, however, preceded by the peak emergence of chironomids, so that the ducklings at Lake Veittijrvi were favoured by the presence of an abundant and accessible high quality food.